2016
DOI: 10.1109/taes.2016.150016
|View full text |Cite
|
Sign up to set email alerts
|

Observability: range-only vs. bearings-only target motion analysis for a leg-by-leg observer's trajectory

Abstract: The aim of so-called range-only target motion analysis (ROTMA) is to estimate the trajectory of a target by a single platform collecting range-only measurements. We focus on the observability analysis when the target is in constant-velocity motion. More precisely, the observability conditions are established when the observer's trajectory is composed of one or several legs. We establish a link between the Fisher information matrix (FIM), and the observability, after having proven the similarity of this matrix … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 18 publications
(36 reference statements)
0
32
1
Order By: Relevance
“…In [8], we showed that when the observer is in CV motion, the trajectory of the target is observable up to an isometry (rotation or axial symmetry). We characterized the set of targets (true target and ghost-targets) O in the same range as the target of interest:…”
Section: The Observer's Trajectory Consists Of One Leg Onlymentioning
confidence: 99%
See 4 more Smart Citations
“…In [8], we showed that when the observer is in CV motion, the trajectory of the target is observable up to an isometry (rotation or axial symmetry). We characterized the set of targets (true target and ghost-targets) O in the same range as the target of interest:…”
Section: The Observer's Trajectory Consists Of One Leg Onlymentioning
confidence: 99%
“…1 depicts the scenario and the 500 estimates (O and T are for the initial positions of the observer and the target, respectively). Because the FIM is singular [8], the CRLB cannot be computed; therefore in Table I the Numerous other simulations with various scenarios allow us to conclude that the MLE is unbiased. But we cannot claim that the MLE reaches the CRLB, because for such scenarios, the FIM is singular.…”
Section: A Observable Scenariomentioning
confidence: 99%
See 3 more Smart Citations